Uruguay : 2010 Article IV Consultation-Staff Report; Public Information Notice; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2011)
In recent years, the IMF has released a growing number of reports and other documents covering economic and financial developments and trends in member countries. Each report, prepared by a staff team after discussions with government officials, is published at the option of the member country.